Methodology for edge detection in high resolution optical satellite image - Rojas Romero, Karin Corina (2021)
Optical satellite images are an important and indispensable tool in the analysis of large areas of land, for this reason many applications arise, among them the subject of the detection of objects present in the images, in order to carry out this task, high resolution images are used. , one of the advantages of these images is the level of detail that can be observed, but they have a disadvantage, which is the coverage, which allows the registration of a limited area, as well as the opportunity for the registration of the image by the satellite depends on the orbit, the time and the weather, all these factors cause that the registration of a specific area is of vital importance, in the present work focuses on presenting a methodology for the detection of edges in high resolution satellite images where evidence of the presence of ships that are present in the image, the technique consists of applying the sobel matrices in their different configurations actions, these found edges can serve as input into pattern recognition systems, as a feature or input to a neural network.